Analisis Sentimen Dan Topic Modelling Dalam Aplikasi Ruangguru - Firdaus, Muhammad Romy; Rizki, Fikri Muhammad; Gaus, Favian Muhammad; Susanto, Indra Kusumajati (STIKOM Tunas Bangsa Pematangsiantar, 2020)
This study aims to determine and analyze responses regarding customer satisfaction Ruangguru Application to the learning space features in the Ruangguru Application at every level of education. This is useful to know the strengths and weaknesses of the Ruangguru Application based on sentiment responses from Ruangguru users. Ruangguru is an online tutoring startup and a technology-based educational content service and provider no. 1 in Indonesia. So of course, customer satisfaction is an important thing that is the goal of the company. So that when customer satisfaction is met, that is where the company can realize their goals. To see how the level of customer satisfaction, sentiment analysis methods and topic modeling are used in processing the data so that responses can be seen as to what is provided by the customer so that it can be an evaluation for the Ruangguru Application.